Attitudes towards risk among maize farmers in the dry savanna zone of Nigeria: some prospective policies for improving food production - Olarinde, L.O.; Manyong, Victor M.; Akintola, J.O. (2007)
This paper applies econometric analyses to quantitatively determine the individual risk attitudes of sampled maize farmers in the dry savanna zone of Nigeria. The extent of the risk attitudes are then made the basis for categorizing the farmers into three groups of low, intermediate and high risk averse maize farmers. This categorization now forms a necessary condition for improving the typology of the farmers, which is hypothesized to be influenced by socio-economic, demographic and other extrinsic “risk factor”. The typology is essentially made possible by discriminant analyses, which re-categorized the farmers into their appropriate risk groups. A four-stage sampling technique leading to the selection of a final sample of about 350 maize farmers was adopted. Results show that, about 8, 42% and 50% of the farmers are respectively lowly, intermediately and highly averse to maize risk. About 72% of the hypothesized variables were found to be responsible for the risk aversion among the sampled farmers. These variables are the basis of policy recommendation to address issues generated by four types of risks identified in maize production namely natural, social, economic and technical risks. These areimportant for harnessing crop technology and to alleviate hunger and poverty in Africa.